2017
DOI: 10.3390/nu9010071
|View full text |Cite
|
Sign up to set email alerts
|

Mass Spectrometry-Based Metabolomic and Lipidomic Analyses of the Effects of Dietary Platycodon grandiflorum on Liver and Serum of Obese Mice under a High-Fat Diet

Abstract: We aimed to identify metabolites involved in the anti-obesity effects of Platycodon grandiflorum (PG) in high-fat diet (HFD)-fed mice using mass spectrometry (MS)-based metabolomic techniques. C57BL/6J mice were divided into four groups: normal diet (ND)-fed mice, HFD-fed mice, HFD with 1% PG extract-fed mice (HPGL), and HFD with 5% PG extract-fed mice (HPGH). After 8 weeks, the HFD group gained more weight than the ND group, while dietary 5% PG extract attenuated this change. The partial least squares discrim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 49 publications
(61 reference statements)
5
17
0
Order By: Relevance
“…Liver is the major organ involved in amino acid metabolism and largely responsible for maintaining amino acid homeostasis. Compared with the control, the amino acid levels were significantly reduced in hamster, which matched the other reports that amino acid levels had dropped by half in the liver of obese mice after 12 weeks of HFD feeding ( Park et al, 2017 ). Importantly, amino acid levels were increased through AEE treatment, indicating AEE might normalize abnormal amino acid metabolisms generated by HFD.…”
Section: Discussionsupporting
confidence: 87%
“…Liver is the major organ involved in amino acid metabolism and largely responsible for maintaining amino acid homeostasis. Compared with the control, the amino acid levels were significantly reduced in hamster, which matched the other reports that amino acid levels had dropped by half in the liver of obese mice after 12 weeks of HFD feeding ( Park et al, 2017 ). Importantly, amino acid levels were increased through AEE treatment, indicating AEE might normalize abnormal amino acid metabolisms generated by HFD.…”
Section: Discussionsupporting
confidence: 87%
“…Uridine and hypoxanthine are pyrimidine and purine derivatives, respectively. Several recent publications have demonstrated that hypoxanthine and uridine could be significantly reduced in the liver of the obese mice under HFD [44], and the hypoxanthine in the feces was also decreased by the microfloral population reduction [45]. Consistent with the above results, levels of uridine and hypoxanthine were lower in the model group than those in the control, indicating that HFD intake could lead the suppression of purine metabolism and pyrimidine metabolism, or the reduction of gut microbiota.…”
Section: Discussionsupporting
confidence: 77%
“…Besides, some biomarkers such as TG(16:0/16:0/22:6), TG(16:0/18:1/22:6), and TG(18:0/16:0/18:1) were also decreased in HFD + EY. A study recently investigated on the effects of dietary platycodon grandiflorum on the liver and serum of hyperlipemia mice and found hepatic lysoPEs with C16:0, C18:0, C18:1 decreased under HFD . This result suggested that the decrease in lysoPE should be accelerated by the formation of both HFD‐induced obesity and pathogenesis of hyperlipidemia.…”
Section: Discussionmentioning
confidence: 99%